Progress in global parallel computing research: a bibliometric approach - Liu, Zhongqiu; Liu, Yaolin; Guo, Yangjie; Wang, Hua (Scientometrics, 2013)
This study adopts a bibliometric approach to analyze the progress in global parallel computing research from the related literature in the Science Citation Index Expanded database from 1958 to 2011. By investigating the characteristics of annual publication outputs, we find that parallel computing has recently experienced increasing attention again after its first rapid development in the 1990s, and the research in this field is entering into a new phase. The distribution of publications indicates that the seven major industrial countries (G7), with USA ranking top, are identified as the most productive and influential countries in this domain. Author keywords were analyzed by comparison, and we conclude that the study focus of parallel computing has shifted from hardware to software, with parallel application and programming based on MPI, GPUs and multicores being the research tendencies; grid computing and cloud computing dominate the distributed computing area due to their heterogeneous and scalable structures; and, furthermore, the processors of parallel machines are heading for a diverse development. The citing - cited matrix brings into light the intense interactions among the disciplines of computer science , engineering , mathematics and physics . The mutual interactions between the four disciplines have increased gradually and reflect the subject characteristics in influence content.